A influência do ambiente institucional e da gestão na formação e controle das Joint Ventures internacionais - Yamasaki, Viviane Eiko Ito (2021)
International joint ventures (IJVs) have been one of the most used entry mode strategies by multinational companies (MNCs) to internationalize and access different foreign markets. However, the decision to establish an IJV involves strategic decisions that can be impacted by internal and external aspects. This thesis aims to investigate the influence of institutional environments and management on the formation and control of IJVs. Three articles were developed in the thesis to achieve this goal, one being a literature review and two empirical studies. The first article investigates the influence of culture on IJVs, seeking to understand how literature has developed over time and to propose a future agenda for current research. From this first article, two quantitative studies were developed based on institutional theory and the perspective of human capital, using a sample of 4,826 IJVs located in Europe and Latin America. Thus, the second article analyzes the formation of the IJVs from the partners’ nationality and quantity, which are relevant aspects of this strategy for establishing the IJVs, but not so much explored in the literature. The third article analyzes the external and internal factors that interfere with the IJVs' shareholding control. In these last two empirical articles, the indirect effects of moderating institutional environments with the management, location, and size of the IJV were investigated, using the analysis of marginal effects, which brought essential findings to the literature. The thesis contributes to the literature, showing the relevance of using the institutional theoretical basis and the human capital perspective for studies on the establishment of IJVs. Additionally, the importance of considering aspects related to the formation of IJVs from the perspective of nationality and the number of partners. Finally, it highlights the need to analyze the moderation of institutional environments related to the formation and property control strategy of IJVs, indicating that they cannot only be analyzed via a direct relationship.